Evaluation of the effects of a team‐based systematic prevention and management program for postoperative orthopedic older patients: A retrospective cohort study - Fumitake Yamaguchi; Chie Inomata; Naoki Yoshinaga; Hirotake Sawada; Kazuko Shimamoto; Ayaka Haruta‐Tsukamoto (PCN Reports)
Abstract Aim This study aimed to evaluate a team‐based systematic prevention and management program for delirium (a multicomponent intervention addressing potentially modifiable risk factors based on the DELirium Team Approach [DELTA]) in older patients undergoing orthopedic surgery within a real‐world clinical setting. The DELTA program was initiated at our hospital in January 2019. Methods A retrospective before–after study was conducted during a preintervention period (January 1, 2017 to December 31, 2018) and a postintervention period (January 1, 2020 to December 31, 2021) at orthopedic wards of an advanced acute care hospital in Japan. A total of 787 inpatients were evaluated before the preintervention period, and 833 inpatients were evaluated after the postintervention period. Results After the DELTA program's implementation, a significant decrease in benzodiazepine receptor agonist prescriptions (odds ratio [OR], 0.39; 95% confidence interval [CI], 0.29–0.53) and an increase in prescriptions of either melatonin receptor agonists or dual orexin receptor antagonists (OR, 3.83; 95% CI, 2.49–5.88) were observed. However, no significant difference was observed in the incidence of falls, self‐extubation, or required level of medical and nursing care, including risky behavior and inability to follow medical or care instructions following the intervention, despite a reduction in the length of hospital stay and institutionalization. Conclusion Implementing the DELTA program for older patients undergoing orthopedic surgery contributed to optimizing the prescription of hypnotics; however, the impact on other patient outcomes, such as falls, self‐extubation, and required level of medical and nursing care was limited.